THE ANALYSIS OF DIGITAL LISTENING MATERIALS IN THE TEXTBOOK “BRIGHT: AN ENGLISH COURSE” - Putra, Adhil Giwana; Yulmiati, Yulmiati (TELL - US JOURNAL, 2025)
In today’s digital age, the use of digital learning materials is essential for fostering language acquisition. This study delves into the quality of digital listening materials within the English textbook. This research aimed to analyze the quality of digital listening materials in the textbook “Bright: An English Course” for eighth-grade students. Employing a content analysis methodology, the study examined the materials using a checklist based on criteria proposed by Cunningsworth (1995) and additional digital standards adapted from Pešikan & Lalović (2023), Hustarna (2023), and Gezer & Anilan (2021). The findings revealed that while the majority of digital listening materials fulfilled the established criteria, as evidenced by the checklist data, significant limitations were identified. The incorporation of diverse listening tasks, contextualized learning, and digital multimedia elements represented positive aspects. However, deficiencies in authentic video content, pre-listening activities, and opportunities for student interaction decrease the materials' potential to optimize listening comprehension and language development. The study concludes that improvements are necessary to enhance the overall quality of digital listening materials within textbooks.